Photo-tunable epsilon-near-zero behavior in a self-assembled liquid crystal – nanoparticle hybrid material. Issue 9 (22nd March 2021) - Bhardwaj, Amit; Sridurai, Vimala; Bhat, Sachin A.; Yelamaggad, Channabasaveshwar V.; Nair, Geetha G.
Abstract : A room temperature stable self-assembled liquid crystal metamaterial exhibits dynamic tuning of the epsilon-near-zero (ENZ) bandwidth on illumination with actinic light in the optical regime. Abstract : Dynamic tuning of electromagnetic response is an important parameter to realize exotic applications of optical metamaterials. Self-assembly achieved via the incorporation of soft materials is an attractive approach to achieve tunable optical properties. Among the soft materials, liquid crystals are highly sought after due to the inherent soft-stimuli responsiveness. This article reports experimental evidence of tunable epsilon-near-zero (ENZ) behavior brought about by an optical field in a self-assembled liquid crystal – nanoparticle system. The material consists of Au nanoparticles capped with a photo-active chiral liquid crystal ligand. In the liquid crystalline state, the system self-assembles into a helical lamellar superstructure, confirmed by polarizing optical microscopy, HRTEM, XRD, and circular dichroism studies. Upon irradiation with UV light, the localized surface plasmon resonance peak of Au red-shifts by ∼10 nm and gets restored with white light illumination. The effective permittivity of the system obtained from ellipsometry indicates ENZ behavior in the visible spectrum with a bandwidth of ∼45 nm which gets enhanced by a factor of 1.6 on UV illumination. Theoretical calculations, carried out using the effective medium approach, support the experimental findings, making the system an efficient ENZ metamaterial in the optical regime.